Potential and the Role of Dispersed Generation in Yangon, Myanmar - Zin Lin, Ohn; Okka, O.; Yi Aye, Hnin (European Journal of Sustainable Development, 2018)
Electricity is the backbone of the development of country’s economy. In Yangon as an economic center of Myanmar, high reliability power supply is the urgent issue. Yangon City uses about 44% of total supply. However, the total generation capacity is reached to its 33-47% due to aging existing power facilities, shortage of fuel for thermal power generation, and output constraint of hydropower generation in dry seasons. Therefore, in the Yangon City where the largest amount of power is demanded in Myanmar, electric power supply hardly meets demand, and load shedding is necessary in dry seasons because potential power demand largely exceeds supply. Moreover, the power transmission and distribution losses in the whole Myanmar reach about 25%, with the transmission loss 7% and the power distribution loss 18% as of 2012. Under the tight supply-demand conditions, there are high needs for improving the efficiency and enhancing electric power supply reliability by reducing the loss rate. In this paper, the solution for load shedding problem and loss reduction is investigated with considering distributed generation. And some potential of energy sources which can solve not only power shortage problem but also environmental problem are also presented. Newton-Raphson method is used for load flow analysis in MATLAB and reliability improvement by DG and feeder replacing is also approached analytically. Keywords: loss reduction, load shedding, Yangon, Dispersed Generation, Load Flow.